The Analysis of Doctors' Workload in the Implementation of Health Services at Boalemo Regency Farmers and Fishermen Hospital - Rasmin Kamumu; Ikram Muhammad; Ghoriqna Wahdah (Journal of Economic, Business, and Administration (JEBA), 2023)
This research aims to find out the workload of Doctors in the implementation of health services at Tani and Fishermen Hospital Boalemo regency. This research uses a descriptive type of research with a quantitative approach. The number of samples analyzed was 12 Doctors from 25 Doctors at Boalemo Regency Farmers and Fishermen Hospital with observation collection techniques, interviews, and questionnaires. Besides, the research results were analyzed with Workload Indicator Staffing Needs (WISN) analysis techniques. The results showed that the available working time of doctors in health services at Tani Hospital and Boalemo Regency Fishermen in each poly is different. The highest available working time in the implementation of health services is the Internal Medicine Specialist with 1,981 hours/year and the lowest Doctor of Heart and Blood Vessels with 161 hours/year. With the highest standard workload activities, doctors in 23,772 hours/year for old patients and 11,886 hours/year for new patients. The lowest workload was 1,806 hours/year for old patients and 1,204 hours/year for new patients. Minimum standard of at most 0.27 or 27% for Pediatricians, Internal Medicine Specialists, Surgical Specialists, Obgyn Specialists, Dental Specialists, Neurologists, Skin and Genital Specialists, and ENT Specialists. Then 0.28 or 28% of the standard of relaxation of ophthalmologists and 0.30 or 30% of the standard of the leniency of Heart and Blood Vessel Specialists from the total working time is available to perform additional activities so that the needs of Doctors in health services at Boalemo Regency Farmers and Fishermen Hospital are 1 Doctor in Poly Surgery, Eye, Heart and Blood Vessels and 2 Doctors in Dental Poly.